The role of education in the self-compilation of asthma control test score in patients with asthma. - Dragonieri, Silvano; Quaranta, Vitaliano Nicola; Scisci, Enrico; Capozza, Elena; Barratta, Federica; De Candia, Maria Luisa; Carpagnano, Giovanna Elisiana (Acta Biomedica Atenei Parmensis, 2022)
BACKGROUND. Asthma Control Test (ACT) is a quick and easy tool that allows physicians to estimate the control of asthma symptoms. Previous studies showed that ACT can be self or physician-administered with similar results.AIM. The aim of our study was to evaluate the role of instruction in the self-compilation of ACT and its difference with the physician-administered modality.METHODS. We enrolled 114 patients with asthma from those attending our outpatient clinic. We divided our population into 3 groups, according to their level of education: 1) low level (primary, middle school; n= 34, age 54.3±11.1), 2) middle level (secondary school; n=44, age 38.2±13.8) and 3) high level (university degree; n=34, age 44.8±14.7). All participants answered the questionnaire in both self- and physician-administered ways. Then, we calculated the parameter ΔACT, defined as the difference between physician-administered and self-administered ACT score. The comparison of ΔACT among groups was assessed by Mann-Whitney U test. Moreover, Spearman correlation was used to assess linear relationship between physician- and self-administered ACT in the three groups.RESULTS. Patients with low and middle education level had higher median ΔACT compared to individuals with high education level (2.17 and 2.15 vs 0.75, p